2015
DOI: 10.1371/journal.pone.0134589
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Alfuzosin as Medical Expulsive Therapy for Ureteral Stones: A Systematic Review and Meta-Analysis

Abstract: BackgroundAlfuzosin has been widely used to treat benign prostatic hyperplasia and prostatitis, and is claimed to be a selective agent for the lower urinary tract with low incidence of adverse side-effects and hypotensive changes. Recently, several randomized controlled trials have reported using Alfuzosin as an expulsive therapy of ureteral stones. Tamsulosin, another alpha blocker, has also been used as an agent for the expulsive therapy for ureteral stones. It is unclear whether alfuzosin has similar effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
2
19
0
1
Order By: Relevance
“…Most of the earlier trials examining α‐blocker therapy for ureteric stones conclude that there is a higher stone clearance and faster stone expulsion time. From 2013 to 2015, multiple meta‐analyses were performed for different α‐blockers (tamsulosin , silodosin , and alfuzosin ) and those results were similar to those of the present review. In a meta‐analysis from 2016 by Hollingsworth et al.…”
Section: Discussionsupporting
confidence: 81%
“…Most of the earlier trials examining α‐blocker therapy for ureteric stones conclude that there is a higher stone clearance and faster stone expulsion time. From 2013 to 2015, multiple meta‐analyses were performed for different α‐blockers (tamsulosin , silodosin , and alfuzosin ) and those results were similar to those of the present review. In a meta‐analysis from 2016 by Hollingsworth et al.…”
Section: Discussionsupporting
confidence: 81%
“…1 2 This endorsement is based on several systematic reviews and meta-analyses of numerous randomized controlled trials, which, in aggregate, showed a higher risk of stone passage among patients treated with alpha blockers (their use has been termed medical expulsive therapy) compared with controls. [3][4][5][6][7][8][9] Consequently, such treatment has become part of the routine management algorithm for ureteric colic.…”
Section: Introductionmentioning
confidence: 99%
“…[12] In many meta-analyses published between 2013 and 2015, it was reported that the rate of stone clearance increased with different alpha-blockers (tamsulosin, silodosin, and alfuzosin), and the expulsion time accelerated. [21,22] However, alpha-blockers have also been shown to increase the risk of major side effects according to the subgroup analysis of placebo-controlled trials and main analysis. [6] On the other hand, a randomized clinical trial suggesting that tamsulosin did not increase passage for ureteral located stones <9 mm was recently published.…”
Section: Discussionmentioning
confidence: 99%